The effectiveness of lycra compression garments on the upper limb in patients with stroke - Naubereit, Carene (My University, 2017)
Introduction: Lycra compression garments have been documented as beneficial in affecting spasticity in children with cerebral palsy but there is little research on the use of Lycra compression garments in adults with neurological conditions. Thus, the purpose of this study was to explore the effectiveness of Lycra compression garments on motor function and functional use of the upper limb, in patients with stroke. Methods: A randomised control design with a control or intervention group was used. Both groups received routine upper limb rehabilitation while the experimental group also received a custom Lycra compression garment worn for a minimum of six hours a day. Results: Change between an initial assessment and assessment at six weeks, was measured on the Fugl-Meyer Assessment of Motor Recovery (FMA) and The Disabilities of the Arm, Shoulder and Hand Outcome Measure (DASH). While both groups had significant improvement in upper limb movement, statistically significant differences for change in total motor function, wrist and hand movement and coordination were found when the experimental group and the control group were compared. Small differences in measurements of pain, passive range of motion, sensation and functional use of the upper limb were found between the two groups. Conclusion: Results indicate that Lycra compression garments may be beneficial in facilitating the return of movement in the upper limb in individuals with stroke.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2017
Keywords: Clothing; Upper Extremity; Patients; Stroke; Polyurethanes